2023
DOI: 10.3390/polym15143009
|View full text |Cite
|
Sign up to set email alerts
|

New Polyvinyl Alcohol/Succinoglycan-Based Hydrogels for pH-Responsive Drug Delivery

Abstract: We fabricated new hydrogels using polyvinyl alcohol (PVA) and succinoglycan (SG) directly isolated and obtained from Sinorhizobium meliloti Rm 1021 via the freeze–thaw method. Both the composition of the hydrogels and the freeze–thaw cycles were optimized to maximize the swelling ratio for the preparation of the PVA/SG hydrogels. During the optimization process, the morphology and conformational change in the hydrogel were analyzed by scanning electron microscopy, rheological measurements, and compressive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…These results indicated that a sufficient amount of -NH 2 probably leads to a strong Schiff base reaction between the polymer components in the hydrogel, which builds a dense structure of the hydrogel and possesses thermal stability [32]. However, the strongest Schiff base reaction occurred in the ACC 4 /DAS hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33]. hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33].…”
Section: Preparation and Characterizations Of Acc/das Hydrogelsmentioning
confidence: 93%
See 2 more Smart Citations
“…These results indicated that a sufficient amount of -NH 2 probably leads to a strong Schiff base reaction between the polymer components in the hydrogel, which builds a dense structure of the hydrogel and possesses thermal stability [32]. However, the strongest Schiff base reaction occurred in the ACC 4 /DAS hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33]. hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33].…”
Section: Preparation and Characterizations Of Acc/das Hydrogelsmentioning
confidence: 93%
“…However, the strongest Schiff base reaction occurred in the ACC 4 /DAS hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33]. hydrogel, which produced the superfluous Schiff base fractures in the second phase and a decrease in the thermal stability [33].…”
Section: Preparation and Characterizations Of Acc/das Hydrogelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Such physical (non-covalent) PVACGs are of a high practical interest in various fields, especially as materials for biomedical applications [ 4 , 5 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. With regard to medical aspects, the use of cryogels based on PVA itself [ 19 , 20 , 22 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and its blends with other (both synthetic and natural) polymers [ 18 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] and composite cryogels that contain entrapped functional disperse fillers [ …”
Section: Introductionmentioning
confidence: 99%
“…Such physical (non-covalent) PVACGs are of a high practical interest in various fields, especially as materials for biomedical applications [4,5,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. With regard to medical aspects, the use of cryogels based on PVA itself [19,20,22,28,[32][33][34][35][36][37][38][39][40][41][42][43] and its blends with other (both synthetic and natural) polymers [18,[44][45][46][47][48][49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%